SIRT6 Promotes Osteogenic Differentiation of Adipose-Derived Mesenchymal Stem Cells Through Antagonizing DNMT1 - Jia, Bo; Chen, Jun; Wang, Qin; Sun, Xiang; Han, Jiusong; Guastaldi, Fernando; Xiang, Shijian; Ye, Qingsong; He, Yan (Frontiers in Cell and Developmental Biology, 2021)
Background: Adipose-derived stem cells (ADSCs) are increasingly accepted as one of ideal seed cells for regenerative medicine for its potential to differentiate into multiple cell types, including osteogenic lineages. Sirtuin proteins 6 (SIRT6) is a nicotinamide adenine dinucleotide (NAD)-dependent deacetylase and plays important roles in a variety of biological processes, including cell differentiation. Methods: Alkaline phosphatase (ALP) activity, ALP staining, and Alizarin Red Staining was performed to explore the roles of SIRT6 in the osteogenic differentiation of ADSCs. Western blot , RT-qPCR, luciferase reporter assay and Co-Immunoprecipitation assay were applied to confirm the relationship between of Sirt6, DNA methyltransferases (DNMTs) and NOTCHs. Results: SIRT6 leads to increased alkaline phosphatase (ALP) activity, enhanced mineralization and upregulated expression of osteogenic-related genes of human adipose-derived mesenchymal stem cells (hADSCs) in vitro and in vivo. Further mechanistic studies showed that SIRT6 regulated osteogenic differentiation of hADSCs depending on its deacetylase activity. SIRT6 selectively prevents abnormal DNA methylation of NOTCH1, NOTCH2 in hADSCs by antagonizing DNMT1. DNMT1 expression was suppressed in SIRT6 overexpression hADSCs, and knockdown partially rescued abnormal DNA methylation of NOTCH1 and NOTCH2, leading to the increased capable of osteogenic differentiation. Conclusions: SIRT6 promotes the osteogenic differentiation of hADSCs. The SIRT6 protein suppresses DNMT level via physical interaction with the DNMT1 protein, deacetylating and destabilizing DNMT1 protein, leading the activation of NOTCH1 and NOTCH2.